P674 Predictors of response to biologics in Crohn's Diseases: A population-based study from the epi-IIRN. (21st January 2022) - Atia, O; Lujan, R; Greenfeld, S; Kariv, R; Matz, E; Dotan, I; Nevo, D; Turner, D
Abstract: Background: Approximately one third of patients with inflammatory bowel disease (IBD) fail to response to anti TNF drugs, and another 25–50% loses response within one year. Identifying prognostic factors of therapeutic failure, may facilitate balancing the risks and benefits of this therapy. In this population-based study, we aimed to explore predictors of therapeutic failure of biologics in Crohn's disease (CD). Methods: We retrieved data from two of four Health Maintenance Organizations in Israel, covering 38% of the population as part of the validated epi-IIRN IBD cohort. We included an inception cohort of CD patients, diagnosed since 2005 who were commenced on biologics. Those who underwent CD-related surgery within 90 days from diagnosis were excluded. The primary outcome was therapeutic failure (i.e. discontinuation of treatment or need for surgery or >1 short steroid courses). The secondary outcome was primary non-response (PNR; i.e. therapeutic failure within 4 months of initiation). Predictors were sought through Cox proportional hazard model. Results: A total of 2, 805 patients were included (923 [33%] pediatric-onset, 1, 882 [67%] adults) with a median follow-up of 7.5 years (IQR 4.4–11.5). The probability of of PNR was 11% and of therapeutic failure 29%, 52% and 62%, after one, three and five years after commencing biologics, respectively. Female sex (HR 1.2 [95%CI 1.1–1.4]), intestinal surgery prior to biologic treatment (HR 1.5 [95%CI 1.1–1.8]) and number of flares prior to biologic treatment (HR 1.1 [95%CI 1.1–1.2]) were associated with therapeutic failure. PNR was associated with intestinal surgery (HR 2.0 [95%CI 1.3–2.9]) and steroid use (HR 1.7 [95%CI 1.3–2.2]). Laboratory blood work, including CRP, ESR, albumin, hemoglobin, leukocytes and platelets, at diagnosis (HR 0.8 [95%CI 0.4–1.5]) and at initiation of biologics (HR 1.1 [95%CI 0.6–1.9]) did not predict therapeutic failure in the multivariable model. Conclusion: Half of CD patients failed to response to biologic treatment within three years. Disease severity prior to biologic treatment, reflected by intestinal surgeries, number of flares and steroid use, predicted therapeutic failure. These results emphasize the importance of timely introduction of intensified treatment in patients at risk.